A study on the epidemiology of brucellosis in bovine population of peri-urban and rural areas of district Multan, southern Punjab, Pakistan - Mian Muhammad Awais; Gohar Khadim; Masood Akhtar; Muhammad Irfan Anwar; Abdul Sammad Ali Khan Shirwany; Ahmad Raza; Abdul Razzaq; Zahida Fatima; Muhammad Amjad Ali; Muhammad Sibtain Bhatti (BMC Veterinary Research, 2024)
Abstract Background Brucellosis is a zoonotic disease caused by a bacterial pathogen belonging to the genus Brucella. It is one of the most frequent bacterial zoonoses globally but unfortunately, it is still considered as a neglected disease in the developing world. Keeping in view, this study was conducted to determine the prevalence and risk determinants of brucellosis in large ruminants of peri-urban and rural areas of district Multan-Pakistan. For this purpose, blood samples (n = 490) were collected from the cattle (n = 245) and buffalo (n = 245) population of the study area and subjected to preliminary screening of brucellosis using local and imported RBPT reagents. All the samples were further analyzed using commercially available multi-specie indirect ELISA kit followed by their confirmation by PCR using genus and species-specific primers. Data obtained from lab analysis and questionnaires were subjected to statistical analysis for Pearson Chi-square, Odds Ratio and Confidence intervals (95%). Results The results showed that the maximum seropositivity was recorded with local RBPT reagent (VRI, Pakistan; 12.45%; 95%CI = 9.72–15.65%) followed by RBPT-IDEXX (12.24%; 95%CI = 9.52–15.45%) and RBPT-ID.vet (11.84%; 95%CI = 9.18–14.95%) however statistical difference was non-significant (P = 0.956). The ELISA results showed an overall seroprevalence rate of 11.22% (95%CI = 8.59–14.33%) with comparatively higher rate in cattle (12.65%; 95%CI = 8.82–17.44%) as compared to buffaloes (9.80%; 95%CI = 6.49–14.15%). The PCR analysis confirmed the presence of genus Brucella in all seropositive samples whereas frequency of B. abortus and B. melitensis in seropositive samples was 80% and 20%, respectively. The co-existence of both species was also observed in 5.45% samples. The statistical analysis showed a significant association of bovine brucellosis with herd size, breed, reproductive disorders, mode of insemination, educational status and farmers’ awareness about brucellosis (P < 0.05). Conversely, locality, age, weight, gender, pregnancy status, parity and puberty status had no associations with brucellosis (P > 0.05). Conclusion In conclusion, brucellosis is prevalent in large ruminants of district Multan, Pakistan. It is suggested to devise and implement stringent policies for the effective control and prevention of brucellosis in the region. Further, the current situation also warrants the need to strengthen interdisciplinary coordination among veterinarians and physicians in one health perspective to ensure and strengthen the human and animal health care systems in the region.